DAMPAK E-COMMERCE DAN SISTEM PEMBAYARAN DIGITAL TERHADAP DAYA BELI BATIK GIRILOYO - Holipa, Lika; Seventeen, Winny Lian; Feroniksa, Anggi Okta; Sipahutar, Roy Refando; Salim, Cindi Fransisca; Syadidah, Qaulan (Mafaza : Jurnal Pengabdian Masyarakat, 2025)
The development of digital technology has driven transformation across various sectors, including micro, small, and medium enterprises (MSMEs). Sentra Batik Giriloyo, as one of the traditional batik centers in Yogyakarta, faces challenges in maintaining its existence amid modern market competition. Limited understanding and application of e-commerce and digital payment systems have become major obstacles to enhancing the competitiveness and purchasing power of the community toward local batik products.This community service program aims to enhance the artisans’ capacity in producing batik within a specific period, including improving the efficiency of the batik-making process, ensuring the availability of raw materials, and optimizing tools and production techniques. It also focuses on utilizing e-commerce platforms and digital payment systems to expand the market and promote local economic growth. The program partners are batik artisans in the Giriloyo area, Imogiri District, Bantul Regency. The methods employed include training, technical assistance, and direct evaluation of implementation. The results of the program indicate that the partners are able to understand the benefits of using e-commerce, manage online stores independently, and utilize digital payment systems such as QRIS and digital wallets. Additionally, the increase in online transactions reflects a rise in consumer purchasing interest. This program has positively impacted the improvement of digital literacy among MSMEs and the purchasing power of the community toward culturally-based local products.